2013
DOI: 10.1186/1475-2840-12-92
|View full text |Cite
|
Sign up to set email alerts
|

Miglitol improves postprandial endothelial dysfunction in patients with acute coronary syndrome and new-onset postprandial hyperglycemia

Abstract: BackgroundHyperglycemia, a risk factor for development of cardiovascular disease, causes endothelial dysfunction. Alpha-glucosidase inhibitors (α-GIs) improve postprandial hyperglycemia (PPHG) and may have favorable effects on associated cardiovascular disease. Effects of α-GIs in patients with acute coronary syndrome (ACS) and PPHG remain unclear; thus, we assessed the effect of α-GI miglitol on endothelial function in such patients by digital reactive hyperemia peripheral arterial tonometry (RH-PAT).MethodsF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…Monocyte chemoattractant protein −3 (MCP-3), tumor necrosis factor β (TNFβ), epidermal growth factor (EGF), interleukin-10 (Il-10) were significantly decreased posttreatment ( † P ≤ .01; * n = 16, for all other markers n = 17) been previously shown with acute dietary and drug interventions. 15,38,39 Importantly the change in lnRHI we report in this study is comparable to these previous trials with the change in lnRHI we described has been reported as impactful for cardiovascular events in adults 28 although the significance of this change in pediatric populations remains to be determined.…”
Section: Pre-vitd Treatmentsupporting
confidence: 89%
“…Monocyte chemoattractant protein −3 (MCP-3), tumor necrosis factor β (TNFβ), epidermal growth factor (EGF), interleukin-10 (Il-10) were significantly decreased posttreatment ( † P ≤ .01; * n = 16, for all other markers n = 17) been previously shown with acute dietary and drug interventions. 15,38,39 Importantly the change in lnRHI we report in this study is comparable to these previous trials with the change in lnRHI we described has been reported as impactful for cardiovascular events in adults 28 although the significance of this change in pediatric populations remains to be determined.…”
Section: Pre-vitd Treatmentsupporting
confidence: 89%
“…Kitano et al [20] reported that short-term miglitol treatment in patients with postprandial hyperglycemia and recent ACS attenuated the postprandial glucose spike, accompanied by improvement of endothelial function. In addition, a previous large randomized controlled trial and a meta-analysis showed that αGI treatment could prevent the development of CV events [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation have been suggested as potential mediators that could link postprandial hyperglycemia, in part through endothelial dysfunction [ 23 - 25 ], to diabetes complications [ 26 - 28 ] although the association of greater peaks with oxidative stress remains to be clearly established [ 29 ]. Individuals with diabetes tend to exhibit high levels of adhesion molecule markers of endothelial dysfunction – ICAM-1, VCAM-1 and E-selectin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%